Melittin promotes dexamethasone in the treatment of adjuvant rheumatoid arthritis in rats - Yang, Linfu; He, Xiying; Zhi, Dandan; Xue, Yunfei; Gong, Xueyang; Dong, Kun; Tian, Yakai (Frontiers in Pharmacology, 2024)
Rheumatoid arthritis (RA) is an erosive-destructive inflammation of the joints, and the chronic, long-term stiffness and deformation induced by RA are some of the symptoms of arthritis that are difficult to treat. Dexamethasone (DEX) and melittin (MLT) are two interesting anti-inflammatory substances, both of which possess anti-inflammatory effects exerted through the suppression of the immune system. The purpose of this study was to explore the role of MLT in the treatment of RA by DEX as well as to clarify the influence of MLT on the efficacy and side effects of DEX. The rats were injected with Complete Freund's Adjuvant (CFA) to induce arthritis, followed by treatment with different doses of DEX and/or MLT. The relevant indexes of paw inflammation were determined, and the appetite, growth status, arthritis status, cytokine levels, and organ coefficient of the rats were evaluated. In addition, the paraffin sections of the joint tissues were prepared to analyze the pathological changes. DEX exhibited side effects, notably hindering feed intake and growth, and inducing immune organ lesions in the rats. MLT significantly reduced the side effects of DEX and promoted its efficacy. DEX in combination with MLT demonstrated a synergistic efficacy in RA treatment, showing advantages in detumescence reduction, pro-inflammatory cytokine inhibition, and joint internal pathological improvement. Thus, MLT promoted the efficacy of DEX in adjuvant RA treatment in rats, offering an approach to reduce the use dosage and side effects of DEX.